What is Health Data?. (4th May 2022) - Rehfeld, Claus; Kreye, Melanie E; Wendelboe, Helena Goldstein; Holm-Larsen, Tove
Abstract : 'Health Data' is a term that is used in many different contexts, but understandings of what it encompasses are at best vague. Without an agreed definition, effective law making, ethical discussions and the development of solutions that relate to Health Data are hindered, and decisions about how and when it can be utilized will be distorted and inconsistent, meaning that the potential value of this important resource for society will not be realized. This study contributes to the healthcare literature by offering an empirical characterization of Health Data, enabling a more rigorous and informed discussion through an exploration of its characteristics and how these can support the formulation of a definition which is functional at an interdisciplinary level. Qualitative interviews with 30 Danish stakeholders working with data and health indicate that a proper definition of Health Data should acknowledge a distinction between when the focus is on the source of the data and when it is on how data is used. Further, it needs to incorporate information relating both to clinical data involving patients and to a population's health status and behaviors more generally. Lastly, it needs to encompass structural data, pertaining to the health system and to wider societal and environmental factors.